Solid-state and solution structural study of acetylacetone-modified tin(IV) chloride used as a precursor of SnO2 nanoparticles prepared by a sol-gel route - Briois, V; Belin, S.; Chalaca, M. Z.; Santos, RHA; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Amer Chemical Soc, 2004)
The effect of addition of different amounts of acetylacetone (acacH) on the species formed at room temperature and after thermohydrolysis at 70 degreesC for 30 and 120 min of ethanolic SnCl4.5H(2)O solutions is followed by EXAFS spectroscopy at the Sn K-edge. We show that thermohydrolyzed solutions are a mixture of SnO2 nanoparticles and soluble tin polynuclear species. The complexation of the tin molecular precursors by acetylacetonate ligands is evidenced by H-1, C-13, and Sn-119 NMR spectroscopy and EXAFS for a acacH/Sn ratio higher than 2. Single crystals are isolated from solution and the structure, determined by X-ray diffraction, is built up from monomeric Cl-3(H2O)Sn(acac)-H2O units bridged together by hydrogen bonding. The acacH/Sn ratio in solution controls the polycondensation of the hydrolyzed species but not the crystallite size of the SnO2 nanoparticles (similar to2 nm). Because of the major presence of chelated tin mono- and dimeric complexes in solution for acacH/Sn > 2, the condensation is almost inhibited, meanwhile the decrease of amount of chelated complexes for the acacH/Sn < 2 gives rise to an increase of the number of nanoparticles.